REPRESENTATION OF THE MESSAGE OF PEACE IN THE FILM KINGDOM OF HEAVEN (2005) - Debiliya, Debiliya; Nurholis, Nurholis; Sudjatnika, Tenny (CALL, 2023)
There were efforts to send a message of peace seem necessary to eliminate all kinds of terrorist stereotypes against Muslims. Many western films were produced to convey the message of peace were made with many attempts. One of these is Ridley Scott's Kingdom of Heaven (2005), set during the Crusades in the late 12th century as a historical piece from the Battle of Jerusalem. This study focused on the character structure of the film Kingdom of Heaven in such a way that the message of peace is conveyed in the film. The study used a qualitative approach combined with the descriptive analysis approach of Charles Sanders Peirce's semiotic theory, called the trichotomy of sign meaning. Data collection techniques using observation, identification and documentation for the film Kingdom of Heaven. The results showed that the image of the message of peace expressed in the film was a war in the name of religion and does not seem to defend a particular religion, but is shaped by different interests. In conclusion, the film determined that not all westerners are good and not all Muslims are bad.Â Keywords: kingdom of heaven, signs messages of peace, Charles Sanders Peirce's semiotic theory